2023
DOI: 10.1101/2023.06.14.545029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatially clustered neurons encode vocalization categories in the bat midbrain

Abstract: Rapid categorization of vocalizations enables adaptive behavior across species. While categorical perception is thought to arise in the neocortex, humans and other animals could benefit from functional organization of ethologically-relevant sounds at earlier stages in the auditory hierarchy. Here, we developed two-photon calcium imaging in the awake echolocating bat (Eptesicus fuscus) to study encoding of sound meaning in the Inferior Colliculus, which is as few as two synapses from the inner ear. Echolocating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In mice, many neurons in the low frequency (presumably dorsal) IC regions respond strongly to vocalizations (Portfors et al, 2009). AM features significantly shape the vocalization selectivity in some of these neurons (Holmstrom et al, 2010), and prominent selectivity to ethologically relevant signals is also observed in the shell IC of bats, rats and gerbils (Holmstrom et al, 2007;Gao et al, 2015;Lawlor et al, 2023). In tandem with our current results, these data imply that a shell IC neural population play important roles in processing and integrating vocal signals, thereby shedding light on the perceptual building blocks of behavioral responses in vocal communication.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, many neurons in the low frequency (presumably dorsal) IC regions respond strongly to vocalizations (Portfors et al, 2009). AM features significantly shape the vocalization selectivity in some of these neurons (Holmstrom et al, 2010), and prominent selectivity to ethologically relevant signals is also observed in the shell IC of bats, rats and gerbils (Holmstrom et al, 2007;Gao et al, 2015;Lawlor et al, 2023). In tandem with our current results, these data imply that a shell IC neural population play important roles in processing and integrating vocal signals, thereby shedding light on the perceptual building blocks of behavioral responses in vocal communication.…”
Section: Discussionmentioning
confidence: 99%